Early Extracorporeal Detoxification after Cardiosurgical Interventions - G. P. Plotnikov; Ye. V. Grigoryev; A. V. Chizhov; B. L. Hayes; L. S. Barbarash (Общая реаниматология)
Objective: to substantiate a need for early use of extracorporeal homeostatic correction techniques during cardiosurgical intensive care. Subjects and methods: A non-randomized study was conducted in 63 cardiosurgical patients with postoperatively evolving multiple organ dysfunction. The clinical efficiency and economic expediency of the early initiation of homeostatic correction were estimated by continuous low-flow venovenous hemofiltration on a Prisma apparatus. Results. The study has demonstrated the advantages of early (within the 36-hour postoperative period) initiation of a procedure by the time of organ dysfunction recovery, the length of stay on a resuscitation bed, and pharmacoeconomic indices. Conclusion. The early (at the stage of dysfunction, until hemostasis becomes stable and in the absence of drainage volume losses) initiation of hemofiltration in the development of multiple organ dysfunction after surgical interventions has been clinically and economically warranted. Key words: extracorporeal homeostatic correction, multiple organ dysfunction, cardiac surgery.